Lightweight high temperature resistant mortar and preparation method thereof
By using specific combined materials and chemical crosslinking technology in lightweight mortar, the problem of mortar prone to cracking under high temperature conditions is solved, and its high temperature, compression and flexural resistance are significantly improved.
Patent Information
- Application Number
- CN202410795075.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-06-19
AI Technical Summary
Existing lightweight mortars are prone to cracking under high temperature conditions, affecting their service life and performance.
The combination of vermiculite, carbon nanotube modified polyurethane, epoxy nanosilica, sand, cement, glass fiber, zeolite powder, polyvinyl alcohol, polycarboxylic acid water reducing agent and water is used to mix and form chemical crosslinking to improve the compressive and flexural resistance of the mortar and enhance its high temperature resistance.
It significantly improves the high temperature resistance, compressive strength and flexural strength of the mortar, ensures that it is not easy to crack under high temperature conditions, and extends the service life.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a lightweight, high-temperature-resistant mortar and a preparation method thereof. Background Art
[0002] Mortar uses various lightweight materials as aggregates, cement as gel material, and some modified additives. It is mixed and stirred to form a mortar, which is widely used in pavement, public buildings, mechanical engineering and other fields; if the pavement temperature is very high, it will cause the pavement to crack, affecting its normal use. For example, patent CN201611258067.0 discloses a masonry mortar. The present invention uses discarded bricks and tiles, which has little pollution to the environment. After 50 freezing and 50 high-temperature water spraying cycles, no cracking or falling off occurs. Sodium dodecyl sulfate can improve the stability of mortar and resist cold weather. Glass fiber can protect against high temperature invasion and can also resist freezing, but it does not improve its high temperature resistance. Summary of the invention
[0003] 1. Technical issues to be resolved
[0004] In view of the deficiencies in the prior art, the present invention provides a lightweight, high-temperature resistant mortar and a preparation method thereof, which has good high-temperature resistance, compressive strength and flexural strength.
[0005] (II) Technical solution
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a lightweight high temperature resistant mortar, comprising the following weight components: 20-30 weight parts of vermiculite, 4-6 weight parts of carbon nanotube modified polyurethane, 2-5 weight parts of epoxy nano-silica, 60-85 weight parts of sand, 50-80 weight parts of cement, 5-12 weight parts of glass fiber, 14-22 weight parts of zeolite powder, 5-10 weight parts of polyvinyl alcohol, 1-2 weight parts of polycarboxylic acid water reducer, and 200-300 weight parts of water.
[0007] Preferably, the preparation method of the carbon nanotube-modified polyurethane comprises the following steps:
[0008] (1) adding 4-hydroxy-5-methyl-1,3-phthalic acid and 3,3-diaminobenzidine to a reactor, and then continuing to add polyphosphoric acid, introducing nitrogen for protection, mechanically stirring, reacting at 170-210° C. for 20-28 hours, cooling after completion, washing with deionized water, filtering, neutralizing with 9-13% ammonia water, filtering, washing with water until neutral, and drying to obtain hydroxylated polybenzimidazole;
[0009] (2) adding hydroxylated polybenzimidazole and 3,3'-dibromo-4,4'-biphenol to N,N-dimethylformamide solvent, stirring and dissolving, adding potassium carbonate catalyst thereto, reacting at 60-75° C. for 12-18 hours, reacting and cooling to room temperature, filtering, washing with distilled water, extracting with ethyl acetate, and drying to obtain intermediate 1;
[0010] (3) adding 8-12 parts by weight of carbon nanotubes to concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 2.8-3.2:1 for acidification to obtain hydroxylated carbon nanotubes; adding acetone solvent to the reactor, introducing nitrogen protection, adding hydroxylated carbon nanotubes and phosphorus oxychloride thereto, reacting for 4-9 hours at 25-50 minutes, adding ice water after the reaction, concentrating, adding ethyl acetate for extraction, drying the organic phase over anhydrous magnesium sulfate, concentrating the filtrate, washing with ether, and then recrystallizing with ethyl acetate to obtain intermediate 2;
[0011] (4) Adding intermediate 2 and intermediate 1 to N,N-dimethylformamide solvent, stirring and mixing, reacting at 95-120° C. for 12-20 h, and then distilling under reduced pressure, cooling to room temperature, filtering and drying to obtain intermediate 3;
[0012] (5) Toluene diisocyanate and polyether polyol are added to a reactor, and then dibutyltin dilaurate is added, and nitrogen is introduced for protection to carry out prepolymerization. The prepolymerization temperature is 70-90°C and the time is 2-4 hours. Then, intermediate 3 is added and stirred for chain extension reaction. After the reaction is completed, the reaction is naturally cooled and discharged to obtain carbon nanotube-modified polyurethane.
[0013] Preferably, the mass ratio of 4-hydroxy-5-methyl-1,3-phthalic acid, 3,3-diaminobenzidine and polyphosphoric acid in (1) is 1:1.1-1.3:0.2-0.3.
[0014] Preferably, the mass ratio of hydroxylated polybenzimidazole, 3,3'-dibromo-4,4'-biphenol and potassium carbonate catalyst in (2) is 1.2-1.5:1:0.02-0.04.
[0015] Preferably, the mass ratio of hydroxylated carbon nanotubes to phosphorus oxychloride in (3) is 1:2-2.4.
[0016] Preferably, the mass ratio of intermediate 2 to intermediate 1 in (4) is 1.3-1.7:1.
[0017] Preferably, the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate and intermediate 3 in (5) is 1:1.2-1.5:0.01-0.02:0.8-1.1.
[0018] Preferably, the preparation method of the lightweight and high-temperature resistant mortar comprises the following steps: adding vermiculite, carbon nanotube-modified polyurethane, epoxy nano-silica, sand, cement, glass fiber, zeolite powder, polyvinyl alcohol, polycarboxylic acid water reducer, and water into a mixer, stirring for 2-10 minutes at a stirring speed of 800-1100 r / min, and obtaining a lightweight and high-temperature resistant mortar.
[0019] (III) Beneficial technical effects
[0020] The invention adds vermiculite, carbon nanotube modified polyurethane, epoxy nano silicon dioxide, sand, cement, glass fiber, zeolite powder, polyvinyl alcohol, polycarboxylic acid water reducer and water into a mixer, and stirs to obtain light high temperature resistant mortar.
[0021] During the stirring and mixing process, the terminal hydroxyl group of the polyurethane and the epoxy group at one end of the epoxy nano-silica undergo a ring-opening reaction to form a stable chemical cross-link, which further improves the compression and flexural resistance of the concrete; and the polyurethane and nano-silica themselves can improve the compression and flexural resistance of the concrete; the polybenzimidazole contained therein has extremely high thermal stability, which can significantly improve the high temperature resistance of the concrete. The polybenzimidazole itself has high compressive strength and tensile strength, which can increase the compression and flexural strength of the concrete; the carbon nanotubes therein can also improve the mechanical properties, high temperature resistance and other properties of the mortar. DETAILED DESCRIPTION
[0022] Example 1
[0023] (1) adding 4-hydroxy-5-methyl-1,3-phthalic acid and 3,3-diaminobenzidine to a reactor, and then continuously adding polyphosphoric acid, wherein the mass ratio of 4-hydroxy-5-methyl-1,3-phthalic acid, 3,3-diaminobenzidine and polyphosphoric acid is 1:1.1:0.2, introducing nitrogen for protection, mechanically stirring, reacting at 170° C. for 20 hours, cooling after completion, washing with deionized water, filtering, neutralizing with 9-13% ammonia water, filtering, washing with water until neutral, and drying to obtain hydroxylated polybenzimidazole;
[0024] (2) adding hydroxylated polybenzimidazole and 3,3'-dibromo-4,4'-biphenol to N,N-dimethylformamide solvent, stirring to dissolve, and continuously adding potassium carbonate catalyst thereto, wherein the mass ratio of hydroxylated polybenzimidazole, 3,3'-dibromo-4,4'-biphenol to potassium carbonate catalyst is 1.2:1:0.02, reacting at 60° C. for 12 h, reacting and cooling to room temperature, filtering, washing with distilled water, extracting with ethyl acetate, and drying to obtain intermediate 1;
[0025] (3) adding 8 parts by weight of carbon nanotubes to concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 2.8:1 for acidification to obtain hydroxylated carbon nanotubes; adding acetone solvent to the reactor, introducing nitrogen protection, adding hydroxylated carbon nanotubes and phosphorus oxychloride thereto, wherein the mass ratio of hydroxylated carbon nanotubes to phosphorus oxychloride is 1:2, reacting for 4 hours at 25 minutes, adding ice water after the reaction, concentrating, adding ethyl acetate for extraction, drying the organic phase over anhydrous magnesium sulfate, concentrating the filtrate, washing with ether, and then recrystallizing with ethyl acetate to obtain intermediate 2;
[0026] (4) adding intermediate 2 and intermediate 1 to N,N-dimethylformamide solvent, wherein the mass ratio of intermediate 2 to intermediate 1 is 1.3:1, stirring and mixing, reacting at 95° C. for 12 h, and then distilling under reduced pressure, cooling to room temperature, filtering and drying to obtain intermediate 3;
[0027] (5) Adding toluene diisocyanate and polyether polyol to a reactor, then adding dibutyltin dilaurate, introducing nitrogen protection, and performing prepolymerization at a temperature of 70° C. for 2 h, and then adding intermediate 3, wherein the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate, and intermediate 3 is 1:1.2:0.01:0.8, stirring for chain extension reaction, and after the reaction is completed, naturally cooling and discharging to obtain carbon nanotube-modified polyurethane;
[0028] (6) Add 20 parts by weight of vermiculite, 4 parts by weight of carbon nanotube-modified polyurethane, 2 parts by weight of epoxy nano-silica, 60 parts by weight of sand, 50 parts by weight of cement, 5 parts by weight of glass fiber, 14 parts by weight of zeolite powder, 5 parts by weight of polyvinyl alcohol, 1 part by weight of polycarboxylic acid water-reducing agent, and 200 parts by weight of water into a mixer and stir for 2 minutes at a stirring speed of 800 r / min to obtain a lightweight, high-temperature resistant mortar.
[0029] Example 2
[0030] (1) adding 4-hydroxy-5-methyl-1,3-phthalic acid and 3,3-diaminobenzidine to a reactor, and then continuously adding polyphosphoric acid, wherein the mass ratio of 4-hydroxy-5-methyl-1,3-phthalic acid, 3,3-diaminobenzidine and polyphosphoric acid is 1:1.3:0.3, introducing nitrogen for protection, mechanically stirring, reacting at 210° C. for 28 hours, cooling after completion, washing with deionized water, filtering, neutralizing with 13% ammonia water, filtering, washing with water until neutral, and drying to obtain hydroxylated polybenzimidazole;
[0031] (2) adding hydroxylated polybenzimidazole and 3,3'-dibromo-4,4'-biphenol to N,N-dimethylformamide solvent, stirring to dissolve, and continuously adding potassium carbonate catalyst thereto, wherein the mass ratio of hydroxylated polybenzimidazole, 3,3'-dibromo-4,4'-biphenol, and potassium carbonate catalyst is 1.5:1:0.04, reacting at 75° C. for 18 h, reacting and cooling to room temperature, filtering, washing with distilled water, extracting with ethyl acetate, and drying to obtain intermediate 1;
[0032] (3) adding 12 parts by weight of carbon nanotubes to concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3.2:1 for acidification to obtain hydroxylated carbon nanotubes; adding acetone solvent to the reactor, introducing nitrogen protection, adding hydroxylated carbon nanotubes and phosphorus oxychloride thereto, wherein the mass ratio of hydroxylated carbon nanotubes to phosphorus oxychloride is 1:2.4, reacting for 9 hours at 50 minutes, adding ice water after the reaction, concentrating, adding ethyl acetate for extraction, drying the organic phase over anhydrous magnesium sulfate, concentrating the filtrate, washing with ether, and then recrystallizing with ethyl acetate to obtain intermediate 2;
[0033] (4) adding intermediate 2 and intermediate 1 to N,N-dimethylformamide solvent, wherein the mass ratio of intermediate 2 to intermediate 1 is 1.7:1, stirring and mixing, reacting at 120° C. for 20 h, and then distilling under reduced pressure, cooling to room temperature, filtering and drying to obtain intermediate 3;
[0034] (5) Adding toluene diisocyanate and polyether polyol to a reactor, then adding dibutyltin dilaurate, introducing nitrogen protection, and performing prepolymerization at a temperature of 90° C. for 4 hours, and then adding intermediate 3, wherein the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate, and intermediate 3 is 1:1.5:0.02:1.1, stirring for chain extension reaction, and after the reaction is completed, naturally cooling and discharging to obtain carbon nanotube-modified polyurethane;
[0035] (6) 30 parts by weight of vermiculite, 6 parts by weight of carbon nanotube-modified polyurethane, 5 parts by weight of epoxy nano-silica, 85 parts by weight of sand, 80 parts by weight of cement, 12 parts by weight of glass fiber, 22 parts by weight of zeolite powder, 10 parts by weight of polyvinyl alcohol, 2 parts by weight of polycarboxylic acid water-reducing agent, and 300 parts by weight of water are added into a mixer and stirred for 10 minutes at a stirring speed of 1100 r / min to obtain a lightweight, high-temperature-resistant mortar.
[0036] Example 3
[0037] (1) adding 4-hydroxy-5-methyl-1,3-phthalic acid and 3,3-diaminobenzidine to a reactor, and then continuously adding polyphosphoric acid, wherein the mass ratio of 4-hydroxy-5-methyl-1,3-phthalic acid, 3,3-diaminobenzidine and polyphosphoric acid is 1:1.2:0.25, introducing nitrogen for protection, mechanically stirring, reacting at 190° C. for 24 hours, cooling after completion, washing with deionized water, filtering, neutralizing with 11% ammonia water, filtering, washing with water until neutral, and drying to obtain hydroxylated polybenzimidazole;
[0038] (2) adding hydroxylated polybenzimidazole and 3,3'-dibromo-4,4'-biphenol to N,N-dimethylformamide solvent, stirring to dissolve, and continuously adding potassium carbonate catalyst thereto, wherein the mass ratio of hydroxylated polybenzimidazole, 3,3'-dibromo-4,4'-biphenol to potassium carbonate catalyst is 1.35:1:0.03, reacting at 67.5° C. for 15 h, reacting and cooling to room temperature, filtering, washing with distilled water, extracting with ethyl acetate, and drying to obtain intermediate 1;
[0039] (3) adding 10 parts by weight of carbon nanotubes to concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3.0:1 for acidification to obtain hydroxylated carbon nanotubes; adding acetone solvent to the reactor, introducing nitrogen protection, adding hydroxylated carbon nanotubes and phosphorus oxychloride thereto, wherein the mass ratio of hydroxylated carbon nanotubes to phosphorus oxychloride is 1:2.2, reacting for 6.5 hours at 37.5 minutes, adding ice water after the reaction, concentrating, adding ethyl acetate for extraction, drying the organic phase over anhydrous magnesium sulfate, concentrating the filtrate, washing with ether, and then recrystallizing with ethyl acetate to obtain intermediate 2;
[0040] (4) adding intermediate 2 and intermediate 1 to N,N-dimethylformamide solvent, wherein the mass ratio of intermediate 2 to intermediate 1 is 1.5:1, stirring and mixing, reacting at 107.5° C. for 16 h, and then distilling under reduced pressure, cooling to room temperature, filtering and drying to obtain intermediate 3;
[0041] (5) Adding toluene diisocyanate and polyether polyol to a reactor, then adding dibutyltin dilaurate, introducing nitrogen protection, and performing prepolymerization, the prepolymerization temperature is 80° C., the time is 3 h, and then adding intermediate 3, wherein the mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate, and intermediate 3 is 1:1.35:0.015:0.95, stirring for chain extension reaction, and after the reaction is completed, naturally cooling and discharging to obtain carbon nanotube modified polyurethane;
[0042] (6) 25 parts by weight of vermiculite, 5 parts by weight of carbon nanotube-modified polyurethane, 3.5 parts by weight of epoxy nano-silica, 72.5 parts by weight of sand, 65 parts by weight of cement, 8.5 parts by weight of glass fiber, 18 parts by weight of zeolite powder, 7.5 parts by weight of polyvinyl alcohol, 1.5 parts by weight of polycarboxylic acid water-reducing agent, and 250 parts by weight of water were added into a mixer and stirred for 6 minutes at a stirring speed of 950 r / min to obtain a lightweight, high-temperature resistant mortar.
[0043] Comparative Example 1
[0044] (1) 25 parts by weight of vermiculite, 3.5 parts by weight of epoxy nano-silica, 72.5 parts by weight of sand, 65 parts by weight of cement, 8.5 parts by weight of glass fiber, 18 parts by weight of zeolite powder, 7.5 parts by weight of polyvinyl alcohol, 1.5 parts by weight of polycarboxylic acid water-reducing agent, and 250 parts by weight of water were added into a mixer and stirred for 6 minutes at a stirring speed of 950 r / min to obtain a lightweight, high-temperature-resistant mortar.
[0045] Comparative Example 2
[0046] Add 25 parts by weight of vermiculite, 3.5 parts by weight of epoxy nano-silica, 72.5 parts by weight of sand, 65 parts by weight of cement, 8.5 parts by weight of glass fiber, 18 parts by weight of zeolite powder, 7.5 parts by weight of polyvinyl alcohol, 1.5 parts by weight of polycarboxylic acid water-reducing agent, and 250 parts by weight of water into a mixer and stir for 6 minutes at a stirring speed of 950 r / min to obtain a lightweight, high-temperature resistant mortar.
[0047] Performance Testing
[0048] After the mortar in each embodiment was laid for 24 hours, the rutting depth was measured at 70°C using the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" to characterize the high temperature resistance. In addition, in order to test the pavement strength, compressive strength and flexural strength tests were also carried out, and the test results are shown in Table 1.
[0049] Table 1: High temperature resistance, compressive strength and flexural strength tests.
[0050] project Rutting depth (mm) Compressive strength(MPa) Flexural strength(MPa) Example 1 0.31 42 10 Example 2 0.28 47 13 Example 3 0.29 44 12 Comparative Example 1 0.42 31 8 Comparative Example 2 0.40 33 9
[0051] It can be seen from Table 1 that the lightweight high temperature resistant mortar of the present invention, Examples 1-3 have lower rutting depth, higher compressive strength and flexural strength than Comparative Examples 1-2, indicating that it has better high temperature resistance.
[0052] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A lightweight high temperature resistant mortar, characterized in that: The invention comprises the following components by weight: 20-30 parts by weight of vermiculite, 4-6 parts by weight of carbon nanotube modified polyurethane, 2-5 parts by weight of epoxy nano-silica, 60-85 parts by weight of sand, 50-80 parts by weight of cement, 5-12 parts by weight of glass fiber, 14-22 parts by weight of zeolite powder, 5-10 parts by weight of polyvinyl alcohol, 1-2 parts by weight of polycarboxylate water reducer, and 200-300 parts by weight of water; The preparation method of the carbon nanotube modified polyurethane comprises the following steps: (1) adding 4-hydroxy-5-methyl-1,3-phthalic acid and 3,3-diaminobenzidine to a reactor, and then continuing to add polyphosphoric acid, introducing nitrogen for protection, mechanically stirring, reacting at 170-210° C. for 20-28 hours, cooling after completion, washing with deionized water, filtering, neutralizing with 9-13% ammonia water, filtering, washing with water until neutral, and drying to obtain hydroxylated polybenzimidazole; (2) adding hydroxylated polybenzimidazole and 3,3'-dibromo-4,4'-biphenol to N,N-dimethylformamide solvent, stirring and dissolving, adding potassium carbonate catalyst thereto, reacting at 60-75° C. for 12-18 hours, reacting and cooling to room temperature, filtering, washing with distilled water, extracting with ethyl acetate, and drying to obtain intermediate 1; (3) adding 8-12 parts by weight of carbon nanotubes to concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 2.8-3.2:1 for acidification to obtain hydroxylated carbon nanotubes; adding acetone solvent to the reactor, introducing nitrogen protection, adding hydroxylated carbon nanotubes and phosphorus oxychloride thereto, reacting for 4-9 hours at 25-50 minutes, adding ice water after the reaction, concentrating, adding ethyl acetate for extraction, drying the organic phase over anhydrous magnesium sulfate, concentrating the filtrate, washing with ether, and then recrystallizing with ethyl acetate to obtain intermediate 2; (4) Adding intermediate 2 and intermediate 1 to N,N-dimethylformamide solvent, stirring and mixing, reacting at 95-120° C. for 12-20 h, and then distilling under reduced pressure, cooling to room temperature, filtering and drying to obtain intermediate 3; (5) Toluene diisocyanate and polyether polyol are added to a reactor, and then dibutyltin dilaurate is added, and nitrogen is introduced for protection to carry out prepolymerization. The prepolymerization temperature is 70-90°C and the time is 2-4 hours. Then, intermediate 3 is added and stirred for chain extension reaction. After the reaction is completed, the reaction is naturally cooled and discharged to obtain carbon nanotube-modified polyurethane.
2. The lightweight high temperature resistant mortar according to claim 1, characterized in that: The mass ratio of 4-hydroxy-5-methyl-1,3-phthalic acid, 3,3-diaminobenzidine and polyphosphoric acid in (1) is 1:1.1-1.3:0.2-0.
3.
3. The lightweight high temperature resistant mortar according to claim 1, characterized in that: The mass ratio of hydroxylated polybenzimidazole, 3,3'-dibromo-4,4'-biphenol and potassium carbonate catalyst in (2) is 1.2-1.5:1:0.02-0.
04.
4. The lightweight high temperature resistant mortar according to claim 1, characterized in that: The mass ratio of hydroxylated carbon nanotubes to phosphorus oxychloride in (3) is 1:2-2.
4.
5. The lightweight high temperature resistant mortar according to claim 1, characterized in that: The mass ratio of intermediate 2 to intermediate 1 in (4) is 1.3-1.7:
1.
6. The lightweight high temperature resistant mortar according to claim 1, characterized in that: The mass ratio of toluene diisocyanate, polyether polyol, dibutyltin dilaurate and intermediate 3 in (5) is 1:1.2-1.5:0.01-0.02:0.8-1.
1.
7. A method for preparing a lightweight, high temperature resistant mortar according to any one of claims 1 to 6, characterized in that: The preparation method of the lightweight high-temperature resistant mortar comprises the following steps: adding vermiculite, carbon nanotube modified polyurethane, epoxy nano-silica, sand, cement, glass fiber, zeolite powder, polyvinyl alcohol, polycarboxylic acid water reducer and water into a mixer, stirring for 2-10 minutes at a stirring speed of 800-1100 r / min, and obtaining the lightweight high-temperature resistant mortar.
Citation Information
Patent Citations
Masonry mortar
CN108264273A
Ultra-high performance concrete and preparation method thereof
CN112430039A
Steel wire net rack insulation board containing modified polyurethane and preparation method of steel wire net rack insulation board
CN117584268A